Pilot-scale acetone-butanol-ethanol fermentation from corn stover - Changsheng Su; Di Cai; Honggang Zhang; Yilu Wu; Yongjie Jiang; Yicheng Liu; Changwei Zhang; Chunling Li; Peiyong Qin; Tianwei Tan (Green Carbon)
Biobutanol is an advanced biofuel that can be produced from excess lignocellulose via acetone-butanol-ethanol (ABE) fermentation. Although significant technological progress has been made in this field, attempts at large-scale lignocellulosic ABE production remain scarce. In this study, 1 m3 scale ABE fermentation was investigated using high inhibitor tolerance Clostridium acetobutylicum ABE-P1201 and steam-exploded corn stover hydrolysate (SECSH). Before expanding the fermentation scale, the detoxification process for SECSH was simplified by process engineering. Results revealed that appropriate pH management during the fed-batch cultivation could largely decrease the inhibition of the toxic components in undetoxified SECSH to the solventogenesis phase of the ABE-P1201 strains, avoiding “acid crash”. Therefore, after naturalizing the pH by Ca(OH)2, the undetoxified SECSH, without removal of the solid components, reached 17.68 ± 1.30 g/L of ABE production with 0.34 ± 0.01 g/g of yield in 1 L scale bioreactor. Based on this strategy, the fermentation scale gradually expanded from laboratory-scale apparatus to pilot-scale bioreactors. Finally, 17.05 ± 1.20 g/L of ABE titer and 0.32 ± 0.01 g/g of ABE yield were realized in 1 m3 bioreactor, corresponding to approximately 145 kg of ABE production from 1 t of dry corn stover. The pilot-scale ABE fermentation demonstrated excellent stability during repeated operations. This study provided a simplified ABE fermentation strategy and verified the feasibility of the pilot process, providing tremendous significance and a solid foundation for the future industrialization of second-generation ABE plants.